Antimicrobial stewardship - what is possible - Pauline Roberts (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
possible. Inappropriate use of antimicrobials has led to resistance, meaning we can no longer rely on them being effective. This is further complicated by a lack of new drugs coming to market. Antimicrobial resistance is a well-documented global problem and threatens low and middle-income countries (LMIC) disproportionately. A "One Health" approach is needed, tackling antimicrobial use inhuman, veterinary, agriculture and environmental sectors. Many health professionals are aware of antimicrobial resistance but struggle to know how to change their practice safely. Here, the author reports on her experience as an antimicrobial pharmacist at Betsi Cadwaladr University Health Board (BCUHB) in Wales and observing practices in Eswatini. BCUHB used various strategies and tools to support prescribers to change prescribing practice.Some of these tools were specifically aimed at primary care prescribers. Similar tools could be developed to support prescribers in LMIC. Antimicrobial resistance cannot be ignored and action is needed now.